Design And Development Of A Novel Tunable Erbium-Doped Fiber Laser - Howieg, Mohammed Alfayturi S (2003)
Widely tunable single channel fiber lasers operating in the l550nm wavelength region are needed as laser source for applications such as wavelength-division-multiplexed (WDM) communication systems, fiber sensors, spectroscopy, and optical fiber gyroscopes. Fiber lasers are emerging as an attractive alternative technology for wavelength-selectable WDM source for direct compatibility with fiber-optic transmission medium, excellent amplifying properties of rare-earth doped fibers, rapidly continuing progress in novel fiber gain media, maturity and robustness of the laser diode pumps used, and availability of fiber-based components. The tunable laser applications of interest in this work have distinct performance requirement, which is the need for wide tunability (the ability to tune the lasing emission through a wide range of wavelengths). In this thesis, the design and development of a single channel continuous wave erbium-doped fiber laser (EDFL), with novel loop mirror configuration, is experimentally studied. Based on design parameters of a fiber laser (launched pump powers, erbiumdoped fiber lengths and output reflectivities of fiber laser), three fiber laser configurations; backward, forward, and bi-directional pumping are demonstrated. Throughout this work different lengths of erbium-doped fiber with various output reflectivities have been examined to extract the optimum output performance of a fiber laser. The performance of the fiber laser is presented in terms of threshold pump power, slope of efficiency, output peak power, linewidth, tuning range, and side mode suppression ratio (SMSR). This new fiber loop configuration exhibits considerably high performance. Output power of 27.7 mW and efficient noise suppression of more than 70 dB have been achieved. A threshold power as low as 2.5 m W and slope efficiency of 20% is realized. Narrow spectral width of 0.058nm over a tuning range of 40 nm is obtained.